ACTIVE TEACHING METHODS IN THE SCHOOL OF YOUNG TEACHER (Pedagogy of Higher and Secondary Education, 2000)
This article is devoted to the problem of searching of active methods of teaching in young teacher's schools, to the pedagogical conditions which provide effective results of usage of a business game in training young teachers for professional activity.Great attention is paid to the active methods such as: pedagogical situations, discussions, conferences.